THE INFLUENCE OF NCT DREAM AS A BRAND AMBASSADOR AND E-WOM ON PURCHASE INTENTION OF TOSTOS PRODUCTS IN DKI JAKARTA THROUGH BRAND IMAGE - Roslyn Brenda Haslimin; Galuh Mira Saktiana (Graduate Program of Universitas Tarumanagara, 2026)
The snack food industry in Indonesia experiences rapid growth every year. TosTos, one of the tortilla chip brands from PT Dua Kelinci, maintaining its brand image and increasing purchase intention, especially after its collaboration with NCT Dream, boy band from Korea. Research aims to analyze the influence of Brand Ambassador, E-WOM on the Buying Intention of TosTos products, through Brand Image. Descriptive quantitative design with purposive sampling for data collection through an online survey of 260 respondents in the DKI Jakarta area. Data analysis was conducted using PLS SEM. The results of this study indicate that Brand Ambassador and E-WOM have a positive influence on brand image and intention to buy. In addition, Brand Image also plays a significant mediating role in the relationship between Brand Ambassador and E-WOM toward Purchase Intention. This research provides practical contributions for companies in developing effective marketing communication strategies, particularly in leveraging public figures and managing consumer perceptions on social media